2019
DOI: 10.1038/s41423-019-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

BCL-6 suppresses miR-142-3p/5p expression in SLE CD4+ T cells by modulating histone methylation and acetylation of the miR-142 promoter

Abstract: The reduced expression of miR-142-3p/5p in CD4 + T cells of SLE patients caused T cell hyperactivity and B cell hyperstimulation. This study aimed to investigate the mechanisms of regulating miR-142-3p/5p expression in SLE CD4 + T cells. The BCL-6 expression was significantly increased in SLE CD4 + T cells compared with normal controls, and the BCL-6 expression was inversely correlated with miR-142-3p/5p expression. BCL-6 suppresses the expression of miR-142-3p/5p by increasing H3K27me3 level and reducing H3K9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 57 publications
4
23
0
Order By: Relevance
“…Our findings suggest that miR-142 regulates aspects of the phenotype of ILC2s associated with their activation state. This is consistent with the reported anti-inflammatory regulatory actions of miR-142 in other lymphocyte lineages (23,30) and with the indication of a negative correlation between ILC2 exposure to activation stimuli (i.e., alarmins) and miR-142 isoform expression levels. Inducible deletion of miR-142 from mature, peripheral ILC2 populations also indicates that ILC2 responses can be modulated postdevelopmentally via the manipulation of miR-142 expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings suggest that miR-142 regulates aspects of the phenotype of ILC2s associated with their activation state. This is consistent with the reported anti-inflammatory regulatory actions of miR-142 in other lymphocyte lineages (23,30) and with the indication of a negative correlation between ILC2 exposure to activation stimuli (i.e., alarmins) and miR-142 isoform expression levels. Inducible deletion of miR-142 from mature, peripheral ILC2 populations also indicates that ILC2 responses can be modulated postdevelopmentally via the manipulation of miR-142 expression.…”
Section: Discussionsupporting
confidence: 91%
“…This is concordant with reported aberrations in miR-142 expression during immune-pathologies (2327) and with its critical role in the maintenance of peripheral immune tolerance (28,29). Importantly, miR-142 expression in lymphocytes such as T cells has been associated with anti-inflammatory actions, with downregulation of expression observed in association with activated cell phenotypes (23,30). Recently, it has been demonstrated that expression of miR-142 isoforms play important roles in the homeostasis of group 1 ILCs (31).…”
Section: Microrna-142 Critically Regulates Group 2 Innate Lymphoid Cell Homeostasis and Functionsupporting
confidence: 88%
“…promoter in SLE CD4 + T cells (Ding et al, 2020). Araki et al suggests that the histone lysine methylation (HKM) modifying enzymes results in changes of the gene expression of RA synovial fibroblasts (Araki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a complicated autoimmune syndrome that is distinguished by perpetuated inflammation and the loss of self-tolerance leading to the production of autoantibodies produced by autoreactive B cells ( 1 , 2 ). The disrupted tolerance and impaired immune responses in patients with SLE cause damage to multiple organ systems.…”
Section: Introductionmentioning
confidence: 99%